Improving the gas oil flow in pipelines by designing new floating technique - Manoharan, M Nerranjini (2012)
Pipeline transportation is always preferred method to transport crude oil and natural gas due to safety purpose and cost effectiveness.Turbulent flow in pipeline causes friction drag and pressure drag which results in reduction in flow rate and pumping power losses.High operational cost is required in order to overcome these problems.As a result,most of the researchers discovered drag reducing agents like additives,polymers,surfactants and suspended solids to solve the problems.In the present work,floating technique will be introduced to improve the gas oil flow. Butyl rubber(IIR)has been selected as the material for floating device based on their flexibilities and strengths. Three sets of butyl rubber (IIR) with 17 stripes have been fabricated according width and thickness of 0.3cm and 0.1cm respectively with different lengths of 10cm,15cm and 20cm. The stripes suspended in pipeline by using aluminium made ring.10 different flow rates of gas oil used to a 1.5 inch sized pipe with testing section lengths of 0.5m, 1.0m, 1.5m and 2.0m. As the floating device suspended in pipeline, it helps to discard the formation of eddies. Among the three lengths of stripes,15cm achieved the highest drag reduction for most of the Reynolds numbers compared to 10cm and 20cm. The optimum drag reduction that can be achieved by using 15cm stripes at Reynolds number of 18173 is 27.93% at testing section length of 2.0m.